2016
DOI: 10.3389/fphys.2016.00464
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Time-of-Day on Maximal Exercise Capacity Is Related to Daily Thermal Balance but Not to Induced Neuronal Activity in Rats

Abstract: In the present study, we investigated whether the daily fluctuations of internal body temperature (Tb) and spontaneous locomotor activity (SLA) interact with the thermal and neuronal adjustments induced by high-intensity aerobic exercise until fatigue. The body temperature and SLA of adult Wistar rats (n = 23) were continuously recorded by telemetry for 48 h. Then, the rats were subjected to a protocol of graded exercise until fatigue or rest on the treadmill during light and dark-phases. Tb, tail skin tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
1
5
1
Order By: Relevance
“…As cold exposure is maintained, heat production is increased and heat loss and production reach a steady state in which T core can be successfully preserved. Therefore, as previously observed with other stressors ( 40 , 44 47 ), it seems that the time-of-day-dependent effects of cold exposure on body temperature reflect the transitory disturbance in heat loss and heat production mechanisms elicited by mixed signals from the internal circadian time and the thermoregulatory pathways that participate in the homeostatic responses.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…As cold exposure is maintained, heat production is increased and heat loss and production reach a steady state in which T core can be successfully preserved. Therefore, as previously observed with other stressors ( 40 , 44 47 ), it seems that the time-of-day-dependent effects of cold exposure on body temperature reflect the transitory disturbance in heat loss and heat production mechanisms elicited by mixed signals from the internal circadian time and the thermoregulatory pathways that participate in the homeostatic responses.…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, Tokizawa and colleagues ( 29 ) observed that the threshold for increased heat production was elevated during the dark phase, while behavioral curling was elicited earlier during the light phase. In rats, a similar effect of time-of-day on thermoregulatory thresholds was also observed during exercise ( 47 ). To our knowledge, this is the first time that a time-of-day effect on the cold defensive response is reported for the rat model.…”
Section: Discussionmentioning
confidence: 69%
“…This afferent (sensory) feedback includes high T CORE levels, a limiting factor for aerobic performance [26,27,58,59]. In particular, higher T CORE values at exercise initiation have been associated with a lower aerobic performance in rats [26,60,61], although this is not a universal finding [56]. In the present study, despite the fact that RSD rats presented greater T CORE at exercise initiation and a higher heat loss threshold than control rats, no differences in T CORE were observed at fatigue.…”
Section: Discussioncontrasting
confidence: 56%
“…Because almost all experimental research is developed in nocturnal rodents, it is a priority to point out if the experiments were developed during their active (night) or passive phase (day) (150). Exercise may also re-entrain circadian rhythms, producing a misalignment that can lead to low cognitive performance, deterioration of alertness, weight variations and sleep disruption (33,(151)(152)(153)(154)(155)(156)(157). Furthermore, forced activity during the inactive phase may disrupt gene expression patterns and hormonal regulations (e.g.…”
Section: Exercise and Light/dark Cyclementioning
confidence: 99%